2006
DOI: 10.1093/ps/85.7.1173
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of body composition, feed intake, and metabolic hormones for broiler breeder females

Abstract: Three hundred twenty Cobb 500 broiler breeder pullets at 21 wk of age were selected from a flock fed according to Cobb Breeder Management Guide specifications. One hundred sixty pullets at 21 wk of age were switched to ad libitum feeding, and the remaining 160 pullets continued to be control-fed. The pullets were photostimulated at 22 wk and maintained until 36.5 wk. Plasma samples were obtained, BW was determined, and hens were killed for determination of body composition at the following periods: 24 h prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
28
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 38 publications
11
28
1
2
Order By: Relevance
“…Ad libitum fed hens had higher levels of plasma glucose, TAG and CHO compared to restricted fed birds. These results are consistent with those reported by Chen et al (2006) and Sun et al (2006).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Ad libitum fed hens had higher levels of plasma glucose, TAG and CHO compared to restricted fed birds. These results are consistent with those reported by Chen et al (2006) and Sun et al (2006).…”
Section: Discussionsupporting
confidence: 94%
“…Ad libitum fed broiler breeders are known to have more hierarchical follicles than their restricted fed counterparts (Yu et al, 1992;Chen et al, 2006;Sun et al, 2006). It seems that higher ovulation rate in ad libitum fed hens with P 4 injection compared to restricted fed birds may be due to more LYF number in their ovary.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the changes in protein levels of PPARg, FAS and ATGL were basically consistent with the changes in mRNA expression. It has been found that changes in feed intake had significant effects on genes expression in the animal for a long time (Richards et al, 2003;Sun et al, 2006). However, NDV infection has more quick and severe changes on gene expression in our study.…”
Section: Discussioncontrasting
confidence: 53%
“…LEP is secreted by adipose tissue and has been shown to play an important role in feed intake regulation, energy metabolism and reproduction in mammals (Sun et al, 2006). Although the chicken LEP promoter gene has not been cloned, chicken LEP is highly conserved and, therefore, is similar to the mammalian gene (Taouis et al, 2001).…”
Section: Discussionmentioning
confidence: 99%